Governance, Order, and Change in World Politics: z wprowadzeniem Boba Jessopa - Rosenau, James Nathan (Journal of Public Governance, 2009)
The article deals with the issue of governance and related systemic limitations, as viewed from the perspective of international relations. In the context of evolving international relations and the increasing interdependence of social systems and subsystems, the author poses a fundamental question as to whether there might be governance without a government - a phenomenon accounted for by invoking interactions along – as well as between – dimensions of an ideological, behavioural and institutional nature.